2023
DOI: 10.22541/au.169685124.46623232/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variable species establishment in response to microhabitat indicates different likelihoods of climate-driven range shifts

Nathalie Chardon,
Lauren McBurnie,
Katie Goodwin
et al.

Abstract: Climate change is causing geographic range shifts globally, and understanding the factors that influence species’ range expansions is crucial for predicting future changes in biodiversity. A common, yet untested, assumption in forecasting approaches is that species will shift beyond current range edges into new habitats as they become macroclimatically suitable, even though microhabitat variability could have overriding effects on local population dynamics. We aim to better understand the role of microhabitat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…In their comprehensive 2021 study, Steven R. Beissinger and Eric A. Riddell highlight the crucial role of physiological traits of species and the availability of suitable habitats in determining the speed and direction of species range shifts (Beissinger et al, 2021). Chardon et al (2023) found that microhabitat variables weakly predict recruitment and seedling survival, with varied responses to environmental factors across species and life stages (Chardon et al, 2023). Adding to this complexity, a recent research has highlighted the importance of considering intraspeci c ecological variation when predicting species distributions for conservation and climate change impact assessment (Varaldo et al, 2023).…”
Section: Older Versions Ofmentioning
confidence: 99%
“…In their comprehensive 2021 study, Steven R. Beissinger and Eric A. Riddell highlight the crucial role of physiological traits of species and the availability of suitable habitats in determining the speed and direction of species range shifts (Beissinger et al, 2021). Chardon et al (2023) found that microhabitat variables weakly predict recruitment and seedling survival, with varied responses to environmental factors across species and life stages (Chardon et al, 2023). Adding to this complexity, a recent research has highlighted the importance of considering intraspeci c ecological variation when predicting species distributions for conservation and climate change impact assessment (Varaldo et al, 2023).…”
Section: Older Versions Ofmentioning
confidence: 99%